An adapted rehabilitation programme for a cross section of South African chronic obstructive pulmonary disease patients - De Klerk, Danelle Ria (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Sport Science))--Stellenbosch University, 2008.